Financial Strategy to Strengthening The Holding Function at PT Pupuk Indonesia (Persero) (The Indonesian Journal of Business Administration, 2020)
This research will explore the financial strategy implemented by PT Pupuk Indonesia (Persero) (PTPI) financial directorate to achieve the main corporate strategy and create value (efficiency) for the corporation. PTPI Finance Directorate is one of the directorates in the PTPI organizational structure that has a very vital and strategic function and role for the running of the corporation so that it must be able to provide business breakthroughs to improve PTPI's performance in the fertilizer SOE holding perspective.The purpose of this research is to answer the right financial strategy questions to strengthen the holding function further, and the value can be created through the financial strategy implemented by the holding company. To answer these research questions, the authors use an external analysis in the form of PEST analysis, porter five's force analysis, competitor analysis, and internal analysis in the form of VRIO analysis and financial analysis. The results of both external and internal analyses produce a SWOT analysis. Using PTPI's SWOT analysis, the direction of the company's business transformation is customer-centric, innovation plant nutrition, solutions and services, best in class in operations and supply chain and activist /functional holding. To achieve this and realize the company's vision, PTPI compiled the main corporate strategy, which was breakdown through strategic initiatives that must be carried out by each directorate.The Directorate of Finance determines the financial strategy in the field of funding, namely, joint borrowers/borrower co-borrower, PTPI bond issuance, and Notional Pooling Account (NPA) and non-financing strategy, namely the joint insurance program. The financial strategy above can support the main corporate strategy's achievement by enhancing and strengthening the holding function, increasing efficiency, and encouraging the development of the non-subsidized fertilizer business and non-fertilizer products owned by PTPI. The implementation of the financial strategy from 2014 - 2019 helped create value (efficiency) for the corporation on a consolidated basis of Rp. 1.42 trillion. To further enhance Good Corporate Governance (GCG) in implementing financial strategies, PTPI Group has issued Funding Guide No. PI-KEU-PD-003 and Joint Insurance Procurement Procedure No. PI-PR-KEU-014. Keywords: holding company, fertilizer, state-owned enterprise (SOE), financial strategy, financing strategy, internal analysis, external analysis, SWOT analysis, value creation, joint borrower, bonds, Notional Pooling Account (NPA), joint insurance.